Tailoring ablation strategies for colorectal liver metastases based upon rat sarcoma viral oncogene mutation status - Calandri, Marco; Odisio, Bruno C. (Chinese Clinical Oncology; Vol 8, No 5 (October 09, 2019): Chinese Clinical Oncology (Molecular Markers in Colorectal Cancer), 2019)
Rat sarcoma viral oncogene (RAS) is one of the most well-known tumor genes implicated in the oncological and surgical management of patients with colorectal liver metastases (CLM). More recently, RAS mutational status has also emerged as a relevant factor affecting the oncological outcomes of CLM treated with ablation procedures, a well-established local therapy modality routinely utilized in the oligometastatic disease (OMD) setting. Available evidence suggests that RAS mutation is a prognosticator of shorter local tumor progression free survival (LTPFS) following liver ablation, and that mutant RAS patients with CLM treated with ablation should have wider minimal ablation margins. In this review, we aim to discuss the current literature on the influence of RAS mutational status on ablation outcomes, as well to provide a perspective on the future research on the impact of tumor molecular biology on liver ablation procedures and the potential synergies between local and systemic therapies.